Highly Enhanced Light–Matter Interaction in MXene Quantum Dots–Monolayer WS2 Heterostructure. Issue 11 (23rd February 2021) - Neupane, Guru Prakash; Wang, Bowen; Tebyetekerwa, Mike; Nguyen, Hieu T.; Taheri, Mahdiar; Liu, Boqing; Nauman, Mudassar; Basnet, Rabin
Abstract: Since the Ti3 C2 was discovered in 2011, the family of MXenes has attracted much attention. MXenes offer great potential in the tuning of many fundamental properties by the synthesis of new structures. The synthesis methods of MXene mainly require steps including immersing a MAX phase in hydrofluoric acid (HF) and processing at high temperatures. However, the HF may be hard to acquire in many countries and processing at high temperatures may cause risk issues. In this article, a simple and cost‐effective synthesis of Ti3 C2 T x quantum dots (QDs) via chemical solution method that follows the long‐time magnetic stirring process‐initiated etching of Al atoms from commercial Ti3 AlC2 powder at room temperature is introduced. With WS2 monolayer sitting over the MXenes QD arrays, a higher level of photoluminescence (PL) enhancement is found in the heterostructure with increasing laser power at room temperature and a few novel quasi‐particles species in the heterostructure at −190 °C. The observations show that the possible plasmonic behavior initiated by QD arrays and the suspension state of WS2 may coplay the roles to trigger multiple quasi‐particles species. This study can be an important benchmark for the extensive understanding of quasi‐particles species, and their dynamics. Abstract : This article presents a simple and cost‐effective synthesis of Ti3 C2 T x MXene quantum dots (QDs) via chemical solution method at room temperature. More specifically, with WS2 monolayer sitting over these MXene QD arrays, a higher level of photoluminescence (PL) enhancement with increasing laser power at room temperature, and a few of novel quasi‐particles species at −190 °C are introduced.